Produção e caracterização de uma quimera recombinante de proteína de superfície de Campylobacter fetus - Balzan, Cláudia (2015)
Bovine genital campylobacteriosis (BGC) is an important venereal disease, caused by Campylobacter fetus subsp. venerealis and related economic losses since it cause reproductive problems in cattle herds. SapA is a surface protein important for the pathogenesis of this bacterium by presenting antigenic variation and be responsible for the persistence of the infection in bovine genital tract. In order to facilitate the laboratory diagnosis of BGC, which involves labor - intensive procedures for collecting and processing the samples, this study aimed to standardize the production of a recombinant chimeric protein and also evaluate their potential as a tool for enzyme-linked immunosorbent assay (ELISA) for sorological diagnosis of BCG in herds. The conserved region of nine homologous sequences of C. fetus sapA gene publicly available was used to design a chimeric synthetic gene, called sapAN78, with 1587 base pairs. The fragment was cloned into pAE plasmid and expressed in Escherichia coli BL21(DE3) pLysS. The recombinant chimera (≈60 kDa) was obtained as inclusion bodies, solubilized in a buffer containing urea and purified by nickel affinity chromatography (Ni+2). The protein was recognized by Western blotting with monoclonal polyhistidine antibodies and with sera from CGB vaccinated cattle and by Dot blotting using bovine sera and hyperimmune serum produced in rabbits. Indirect ELISA based on the recombinant protein purified has been standardized and tested 219 sera samples from cattle. The sensitivity and specificity of this assay were 90.91% and 89.78%, respectively. Therefore, rSapAn78 has potential as antigen for indirect ELISA for serological diagnosis of C. fetus in cattle.